Modernisasi dan Penguatan Perekonomian ‘Aisyiyah Pada Masa Kepemimpinan Siti Baroroh Baried 1965-1985 M: Modernization and Strengthening of the Economy of 'Aisyiyah During the Leadership Period of Siti Baroroh Bared 1965-1985 AD - Febriyani, Halimah Nur (Nur Science Institute, 2021)
This study discusses the organization of 'Aisyiyah during the leadership of Siti Baroroh Bared, in which in her leadership she succeeded in making 'Aisyiyah known and collaborating with international organizations. This article will reveal the condition of 'Aisyiyah before the leadership of Siti Baroroh Bared and how the development of 'Aisyiyah during her leadership. The method used in this research is the historical method. Siti Baroroh Bared has a high intellect so that she can create superior and new programs in an 'Aisyiyah organization including the development of the Bustanul Athfal Kindergarten, establishing a school for midwives and nurses, conducting recitations by traveling outside the Kauman village, the existence of an Economic Business Entity program The 'Aisyiyah family (BUEKA), conducts regeneration and leadership coaching and training programs, organizes compensation programs for orphans and the poor, in addition to cooperating with various parties or organizations and establishing several federations of women's organizations